Incidence and Predictors of Inpatient Mortality Rate After Cases Started Care in the Intensive Care Unit in Debre Markos Referral Hospital - Tesfaye Shumet; Fassikaw Kebede (SAGE Publishing, 2023)
Background The intensive care unit (ICU) is a separate area in which potential health care services for patients who are in critical condition with detailed observation, monitoring, and advanced treatment than other units. This study aimed to assess the incidence and predictors of inpatient mortality after inpatient treatment was started in Debre Markos Comprehensive Specialized Hospital. Methods A facility-based retrospective cohort study was employed among 384 ICU-admitted patients from December 30, 2020 to January 1, 2022. The collected data were entered into Epi Data version 4.2 and exported to STATA 14.0 for further analysis. The Cox proportional hazard regression model was fitted after checking using the Schoenfeld residual and log-log plot test. A categorical variable with an adjusted hazard ratio of 95% CI was claimed for predictors. Result Overall, 384 admitted adult patients were included in the final analysis with a mean (±SD) age of 42.1 (±17.1) years. At the end of the follow-up period, 150 (39.06%) cases died in the ICU. The overall incidence of the mortality rate was 16.9 (95% CI: 13.7-19.55) per 100 person per day. Epidemiologically, 347 (90.36%) cases were medical illness, 25 (6.51%) surgical, and 12 (3.13%) were obstetric cases, respectively. The median length of inpatient stay was found to be 4.9 (IQR  ±  2.8) days. In multivariable analysis; being (+) for human immunodeficiency virus (AHR  =  0.59, 95% CI: 0.39-0.91), age ≥65yearas (AHR  =  1.61, 95% CI: 1.11-2.32), and admission on weekend-time (AHR  =  1.48, 95% CI: 1.06-2.06) were predictors of inpatient death. Conclusion The overall in-hospital mortality rate was significantly higher than in the previous study in this hospital with a short median survival time. The inpatient mortality rate was significantly associated with age ≥65 years, being HIV positive, and admission during weekend time. Therefore, effective intervention strategies should be highly needed for ICU team members for early risk factors prevention.